Simulation-Based Learning in Emergency Nursing Practice: A Phenomenological Study - La Ramba, Hardin; Tapit, Olivia P.; Wowor, Tommy Jemmy Fansiscus; Yari, Yarwin; Monteiro, Elizabeth; Butar Butar, Samsinar; Baua, Elizabeth C.; Lorica, Josephine Daquioag D.; Pizzaro, Jessus B.; Dator, Wireen Leila T.; Villagracia, Hezel N.; Adolfo, Melenie Reboldera; Al-Azri, Aisha Sultan Hamood (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Simulation-based learning (SBL) is widely used in nursing education, especially in high-risk settings such as emergency departments. However, limited qualitative research has explored how emergency nurses experience simulation in clinical practice.Purpose: This study aimed to explore emergency room nurses’ lived experiences of simulation-based learning and to understand how simulation contributes to their professional development and clinical practice.Methods: A descriptive phenomenological approach was used. Ten emergency room nurses from a public hospital under Oman’s Ministry of Health were recruited using purposive sampling. Data were collected through in-depth interviews and analyzed using Colaizzi’s seven-step phenomenological method to identify the meaning of participants’ experiences.Results: Three themes emerged from the analysis: (1) simulation as a bridge between theory and clinical practice, where simulation enabled nurses to translate theoretical knowledge into practical decision-making in realistic emergency scenarios; (2) developing professional confidence and clinical competence, where repeated simulation practice strengthened clinical skills, preparedness, and confidence; and (3) simulation as a strategy for improving nursing services, where participants perceived simulation as contributing to improved clinical performance, teamwork, and patient care quality. Participants also identified practical challenges, including scheduling constraints and workload demands, which limited participation in simulation activities.Conclusion: Simulation-based learning is experienced by emergency nurses as a meaningful experiential learning process that supports the integration of theoretical knowledge with clinical practice. In addition to improving individual competencies, simulation contributes to professional confidence, teamwork, and the quality of emergency care. Further research across diverse healthcare settings is needed to explore its long-term impact on nursing practice and patient outcomes.